Immunological Effects of Acute Testicular Torsion on the Contralateral Testis in Rats - Schanaider, A.; Aiex, C. A.; Errico, G. (European Journal of Pediatric Surgery, 2011)
The mechanism by which unilateral testicular torsion leads to injury of the contralateral testis is still controversial. The present study aimed to evaluate immunohistopathological changes in the contralateral testis of rats after acute testicular torsion.40 pubertal rats were randomly divided into 3 groups. Group 1 (n=10) functioned as controls. Group 2 rats (n=10) underwent a sham operation, and Group 3 (n=20) underwent 720° torsion of the left spermatic cord (3 h) followed by detorsion (24 h). Immunofluorescence tests were done to investigate contralateral lesions in half of the animals in Group 3. Nitro blue tetrazolium (NBT) was injected in both testes to identify the presence of oxygen-derived free radicals. 24 h after reperfusion, bilateral samples of the testes were obtained for histological analysis. Fisher’s exact test was used for statistical analysis with p-values < 0.05 considered significant.Immunofluorescence tests were positive for the contralateral (right) testis but with a lower intensity than that of the testis submitted to torsion. NBT reaction was intense all over the left testis while a minor reaction was visible in the right testis. In Group 3 the left distorted testicle showed diffuse edema with cell elimination and extensive necrosis of the seminiferous tubules. Histological lesions were moderate to mild in the contralateral testis.An autoimmune IgG-mediated mechanism deposited on the basement membrane of seminiferous tubules seems to be involved in the genesis of contralateral testis injury.
Keywords: testis; spermatic cord torsion; autoimmune response; animal experiment